KAJIAN ABRASI PANTAI DAN KONDISI LINGKUNGAN SOSIAL MASYARAKAT DI DISTRIK KOFIAU KABUPATEN RAJA AMPAT - Frits Ambarau; Hilda Vemy Oroh; Irfan Rifani (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2021)
Coastal abrasion in Kofiau District, Raja Ampat Regency has an impact on physical damage to the coastal landscape and the impact on the social environment, namely the interaction of the physical-social environment and the changes in social life that accompany it. The purpose of this study was to determine the impact of coastal abrasion and its effect on the social environment of the community in Kofiau District, Raja Ampat Regency. The research method used is qualitative. There were six sources of information consisting of village heads, community, religious leaders, education leaders, youth, and the community establishing coastal abrasion. Data collection techniques used are observation, interviews, and documentation. The analysis technique is carried out by data reduction, data presentation, and concluding each research data. The results showed: 1) there was damage to the landscape as part of the physical condition of the abrasion beach, namely the erosion of land along the coast, people losing their homes and homestays, damaged village connecting roads, and the destruction of wave barriers. 2) some people lost their jobs in the tourism sector as a result of the destruction of homestays and cafes as a means of supporting tourism activities. 3) some people want to use relocation to a safer place, but choose to survive because life has merged with coastal life. 4) efforts to reduce the impact of abrasion are the construction of embankments, maintenance of coral reefs, and planting of mangrove trees.